ANALYSIS OF BUSINESS UNIT DEVELOPMENT STRATEGY OF PT. PEMBANGUNAN ACEH (PEMA) - Sari Yulis Terfiadi; Zulfan; Muhammad Jais; Ishak Sanusi; Farid Haikal (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Improving the economy and investment in Aceh province must be adjusted to the potential and social structure. Investments that are in line with the social structure and economic capacity of the local community can sustain Aceh's economic growth. The investment development process must be responded to quickly by the government, which has legal authority to implement various types of programs. One strategy to reduce Aceh's poverty rate is to maximize Aceh-Owned Enterprises (Badan Usaha Milik Aceh - BUMA), a business holding company with the Aceh government owning the majority (100%) of its capital and shares. The holding company named PT. Pembangunan Aceh (PEMA) aims to improve development, the economy, and Aceh's locally generated revenue. For this reason, a potential business analysis strategy is needed to be developed by PEMA in compliance with Aceh Qanun No. 5 of 2019 concerning Capital Participation of the Aceh Government in Aceh-Owned Enterprises (BUMA) and the format or scheme of capital participation or business scheme that is feasible to develop company profit and the sustainability of PEMA for the future. This study uses a qualitative method with a descriptive phenomenological approach through in-depth interviews and observations of informants on the PEMA business unit development strategy, namely commissioners and directors, academics, and the Aceh Investment Promotion Agency and One Stop Services. The Business Model Canvas (BMC) model and SWOT analysis are used in the data analysis process. This study found that the PEMA agro-industry sector business unit model has great potential to be developed with the building of a biodiesel factory. Additionally, this business unit empowers the welfare of Acehnese oil palm farmers.